Neonatal meconium aspiration: risk factors and adaptation by the newborns - I. M. Bogomazova; A. N. Strizhakov; I. V. Ignatko; V. S. Belousova; E. V. Timokhina; E. G. Pitskhelauri; M. A. Kardanova; N. V. Spiridonova (IRBIS LLC, 2019)
Aim: to identify the risk factors of meconium aspiration and study its impact on neonatal adaptation. Materials and methods. Medical records of 44 women and their infants were studied. Results. In 85 % of cases, the diagnosis of complicated pregnancy was made, in 100 % cases - there was a complicated delivery; 100 % of newborns were put on mechanical ventilation, 95 % of them were diagnosed with cerebral depression syndrome, and 72.5 % - with aspiration pneumonia. Conclusion. A differentiated approach to the management of pregnancy and labor will reduce perinatal morbidity.